A Care Ethics Approach to Digital Literacies: Supporting Language Acquisition, Identity, and Overall Well-being of Adult EAL Learners with Refugee Experiences in Canada - Shanna Baslee (BC TEAL Journal)
Academics around the globe have examined the ethics of care theory and its application across various educational contexts; however, little research has focused on this approach within the adult English as an additional language (EAL) context. Additionally, educational research on digital literacies has examined the competencies necessary to be digitally literate today, yet only recently has research in EAL contexts shed light on the digital needs and goals of adult newcomers with refugee status in Canada. This review provides insight into the pairing of a care ethics approach with digital literacies instruction for learners with refugee experiences in the EAL classroom. Through current research and classroom practices, I argue that this approach can support language acquisition, identity, and overall well-being for this growing population of adult learners in Canada. Synthesizing research on a care ethics approach in education and the digital literacy needs and goals of adult English language learners, the first section focuses on the role of a care ethics approach in EAL contexts. The second section discusses the digital landscape in Canada and summarizes research on digital literacy practices in EAL contexts. The final section brings forth the discussion, strategies, and implications of integrating a caring, empathetic, and inclusive approach to digital literacies.